Two-Sided Approximation of Solutions of a Multipoint Problem for an Ordinary Differential Equation with Parameters - Mentynskyi, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We construct an algorithm for the two-sided approximation of a solution of a multipoint boundary-value problem for a quasilinear differential equation under assumptions that are two-sided analogs of the Pokornyi B-monotonicity of the right-hand side of the equation. We establish conditions for the monotonicity of successive approximations and their uniform convergence to a solution of the problem.